2021
DOI: 10.1038/s41598-021-91799-8
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor dysfunction one year after first childbirth in relation to perineal tear severity

Abstract: The aims of this study were to evaluate pelvic floor dysfunction symptoms one year after delivery and investigate whether adverse functional outcomes after childbirth were related to the degree of perineal injury. A prospective cohort of 776 primiparas were included. Self-reported pelvic floor function data were obtained using a web-based questionnaire. Women with no/first-degree injuries, second-degree injuries, third-/fourth-degree injuries (obstetric anal sphincter injury, OASI) and cesarean section were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 34 publications
0
33
0
1
Order By: Relevance
“…Our results showed additional benefits of an online supervised exercise program in healthy pregnant individuals (including weekly guidelines on a healthy lifestyle), which may be key to reducing childbirth trauma to the pelvic floor and in the immediate postpartum recovery period to prevent comorbidities such as dyspareunia, sexual dysfunction, or urinary incontinence throughout life [44][45][46]. Previous studies have suggested that individuals who practice exercise are less likely to suffer tears with less severity as well as an episiotomy.…”
Section: Discussionmentioning
confidence: 64%
“…Our results showed additional benefits of an online supervised exercise program in healthy pregnant individuals (including weekly guidelines on a healthy lifestyle), which may be key to reducing childbirth trauma to the pelvic floor and in the immediate postpartum recovery period to prevent comorbidities such as dyspareunia, sexual dysfunction, or urinary incontinence throughout life [44][45][46]. Previous studies have suggested that individuals who practice exercise are less likely to suffer tears with less severity as well as an episiotomy.…”
Section: Discussionmentioning
confidence: 64%
“…In addition, the participants wished to be able to report birth-related complications other than perineal tears, which suggests that the grade of perineal tearing is not the only factor impacting birth experience and birth-related problems for women. Studies have confirmed that higher grade of perineal tear increases the risk of postpartum pelvic floor dysfunction, but adverse functional effects are experienced by women with perineal lacerations of all grades, as well as by those with an intact perineum [ 21 ]. Second-degree trauma has been shown to be a risk factor for urinary incontinence, whereas inflammatory states and infections can be possible causes of dyspareunia [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that higher grade of perineal tear increases the risk of postpartum pelvic floor dysfunction, but adverse functional effects are experienced by women with perineal lacerations of all grades, as well as by those with an intact perineum [ 21 ]. Second-degree trauma has been shown to be a risk factor for urinary incontinence, whereas inflammatory states and infections can be possible causes of dyspareunia [ 21 ]. Therefore, it is important to take other types of complications into account, such as infections of the urinary tract or uterus, pain in the pelvis and the tailbone, hemorrhoids, and nerve injuries.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been assumed that women with severe perineal tears have the highest risk of morbidity compared to women with a first-or second-degree perineal tear, thus, research has focused on long-term consequences for women after third-or fourth-degree tears [3]. Regardless of severity of the perineal tear, studies indicate that women can experience symptoms of PFD, such as a feeling of wide vagina, bowel emptying difficulties, dyspareunia, and perineal pain many years after vaginal birth [4][5][6]. This may possibly be due to a deficient perineum causing a loss of support of the pelvic floor.…”
Section: Introductionmentioning
confidence: 99%